Polarimetrični temperaturni senzor - Završnik, Miha (Informacije MIDEM, 1997)
Temperature is one of the most important prameters to be measured in industrial process control. The primary reason for interest in industrial fiber optic temperature sensors is their electromagnetic immunity and electrical passivity. This enables the use of fiber optic sensors in electromagnetically hostile and hazardous environments. During the last decade, many intrinsic optical fiber temperature sensors have been proposed using the Michelson or Mach-Zehnder configuration. However, those interferometers suffer low selectivity and require a well isolated and undisturbed reference arm that is very hard to produce. An alternative to the classic interferometry is a polarimetric sensor which uses the interference of two polarization eigenmodes in high birefringence fibers. We theoretically and experimentally investigated the influences of the sensing and lead fiber length, the extinction ratio of the input polarizer and the coherence properties of the light source for polarimetric temperature measurements. We have shown that there is a possibility to construct a relatively simple and inexpensive fiber optic polarimetric thermometer for absolute temperature measurements by using a low ER polarizer and a low cohernet source. The proposed polarimeter does not exhibit high sensitivity. However, it is easy to achieve a large unambigous range with a resolution below 0.1 oC which satisfies most demands in many industrial and medical applications.
Keywords: meritve; optični sistemi; regulacija; senzorji; temperatura